2013
DOI: 10.1158/0008-5472.can-12-3070
|View full text |Cite
|
Sign up to set email alerts
|

Midkine Promotes Neuroblastoma through Notch2 Signaling

Abstract: Midkine is a heparin-binding growth factor highly expressed in various cancers, including neuroblastoma, the most common extracranial pediatric solid tumor. Prognosis of patients with neuroblastoma in which MYCN is amplified remains particularly poor. In this study, we used a MYCN transgenic model for neuroblastoma in which midkine is highly expressed in precancerous lesions of sympathetic ganglia. Genetic ablation of midkine in this model delayed tumor formation and reduced tumor incidence. Furthermore, an RN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 49 publications
0
61
0
Order By: Relevance
“…Recently, we and others have shown that the secretion of MK in tumor cells may serve as biomarker for gastrointestinal tumors and glioblastomas (10,11). Therefore, the development of MK inhibitors has been considered as an attractive idea to prevent tumor growth and antiapoptosis in cancer cells (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others have shown that the secretion of MK in tumor cells may serve as biomarker for gastrointestinal tumors and glioblastomas (10,11). Therefore, the development of MK inhibitors has been considered as an attractive idea to prevent tumor growth and antiapoptosis in cancer cells (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…67) Midkine-notch2-HES1 signal axis also plays a critical role in neuroblastoma tumorigenesis. 93) Similarly, notch-HES signal was found to be active in the PTN promoted hematopoietic stem cell expansion and regeneration, while the downstream signal of HES here is PI3K/AKT. 21) Nuclear Targeting Pathway The mitogenic and antiapoptotic function of MK are also realized though its internalization, cell nuclear targeting and the subsequent transcription promotion.…”
Section: )mentioning
confidence: 80%
“…NOTCH2 is a first neighbour of the NSCLC-related Midkine (MDK) protein, which is expressed only in NSCLC and not in normal lung, and it is a known NSCLC biomarker 52. MDK can also cause neuroblastoma through activating specifically NOTCH2 53. LFNG acts like a double-edged sword: by promoting both the Delta1 ligand activated NOTCH1/2 receptors and decreasing the Jagged1 ligand activated NOTCH1 signalling, it contributes to the normal and tumour suppressor effect of NOTCH1 51.…”
Section: Resultsmentioning
confidence: 99%